Recovering from the Ebola crisis: 'Social Reconnection Groups' in a rural Liberian community. (2019) - Morelli, M.; Cyrus, G.; Weissbecker, I.; Kpangbai, J.; Mallow, M.; Leichner, A.; Ryan, E.; Wener, R.; Gao, J.; Antigua, J.; Levine, A. C.; Feuchte, F.
Abstract : In 2014/2015, International Medical Corps (IMC) operated two Ebola Treatment Units (ETUs) in Liberia and three in Sierra Leone when the Ebola virus disease epidemic killed over 11, 000 people across Liberia, Sierra Leone and Guinea. As Ebola cases declined in Liberia, IMC Psychosocial teams transitioned to working in communities highly affected by the epidemic. This article describes IMC's experience with developing and implementing a community-based mental health and psychosocial group intervention in a rural, severely affected Liberian town – Mawah – where 46 out of approximately 800 community members were infected, 39 of whom died. In this paper, we present how the group intervention, named 'Social Reconnection Groups', was developed and implemented. We then discuss intervention strengths, challenges, key lessons learnt and recommendations for how Social Reconnection Groups can be adapted for use in similar settings.